Perancangan Perangkat Lunak Segmentasi Citra Luka Kronik Dengan Menggunakan Algoritma Metode Fuzzy C-Means - Ali Mubaro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The process of segmentation in digital images that separates an object from the background or background can be obtained from the RGB value in each pixel on a digital image so that the object can be processed for other purposes. Along with the development of technology in applications that process digital images, the process of segmentation is becoming increasingly necessary. The results of segmentation must also be more accurate because if the segmentation results are inaccurate it will affect the results of the next process. In general, the segmentation process is divided into three parts based on classification, based on edges and by region. From an image information can be obtained in accordance with the interests, but sometimes on existing images can not be obtained directly the information needed. There are times when it is difficult to process information from an image directly in plain view by only relying on the sense of sight. This is understandable, considering that the image is a large collection of dots of color. One alternative to help display and process this information is by segmentation.